Alternative Organizing and (In)Visibility: Managing Tensions of Transparency and Autonomy in a Nonprofit Organization. (November 2015) - Jensen, Peter R.; Meisenbach, Rebecca J.
Amid recent attention to alternative and hidden organizations, empirical studies have thus far tended to focus on large, well-known organizations in contrast to lesser known, local, and partially hidden organizations. Organizations that hide face several advantages and disadvantages, and this article seeks to examine how one nonprofit organization manages the benefits and obstacles of being partially hidden. Using ethnographic field methods and semi-structured interviews, we analyze how one homeless shelter's visibility fluctuates in relation to its goals. We argue that by operating as a shadowed or shaded organization, this shelter is resisting trends toward organizational transparency that are especially powerful in the nonprofit sector. The findings highlight how the organization manages tensions of (in)visibility to maintain autonomy, while still securing support from external organizations. The results have implications not only for studying hidden organizations, but also for alternative and nonprofit theorizing.